NEWTON’S TYPE QUANTUM FRACTIONAL INTEGRAL INEQUALITIES PERTAINING TO n-POLYNOMIAL CONVEX FUNCTIONS AND APPLICATION - Liko, Rozana; Kashuri, Artion (Matematichki Bilten, 2023)
In this paper, we consider a new Newton’s type quantum fractional integral identity. Following that as an auxiliary result, we established in our main results some integral inequalities of Newton’s type including \(n\)-polynomial convex functions. From our main results, we discuss in detail several special cases. Finally, an example and application of a special means of positive real numbers are presented to support our theoretical results.